CALON PERSEORANGAN : PERGESERAN PARADIGMA KEKUASAAN DALAM PEMILUKADA - Retno Saraswati (Masalah-Masalah Hukum, 2011)
The justice's argument and welfare which buiided by Mahkamah Konstitusi whose grant opened the independent stripe is already moved power paradigm in local election. The rubbing from old paradigm who seat political party as on of access in nomination of head or deputy of a district to be a new paradigm that the power in nomination of head or deputy of a distric not finished to divided by political party, but that power also give truth for individual to participant in nomination of hear or deputy of a district Kata kunci: Calon Perseorangan, Pemilukada